The joy luck club - Wang, Wayne, 1949-; Tsai Chin, 1938?-; Ki{u18E5}u Chinh, 1939-; Lu, Lisa.; Tan, Amy.; Hollywood Pictures; Oliver Stone (Burbank, CA : Buena Vista Home Video, 2002)
The stories of four native-born Chinese women and their American-born daughters, showing the influence each has on the others' lives, and how they are the same and different
Based on the novel by Amy Tan
Executive producer, Oliver Stone, Janet Yang ; screenplay, Amy Tan & Ronald Bass ; music, Rachel Portman
Cast : Tsai Chin, Kieu Chinh, Lisa Lu.
Keywords: Tan, Amy -- Film and video adaptations; Mothers and daughters -- United States -- Drama; Chinese Americans -- Drama; Women -- China -- Social conditions -- Drama; Film adaptations; Video recordings for the hearing impaired; Feature films